Finding a Balance Between Public and Private Spaces in Student Housing Design in Thailand - I Awal, Sajid (Nakhara : Journal of Environmental Design and Planning, 2022)
Public and private spaces are of equal importance in promoting social interaction and ensuring self-contemplation for users of student housing. This research aims to establish the right balance among the public and private spaces as it is arguably one of the difficulties in housing design. A housing design is proposed for students of Chulalongkorn University in Bangkok, analyzed, and justified following the research findings to derive the desired balance between the public and private spaces. Several sets of literature of related work are undertaken as part of the qualitative design. At the same time, space syntax is used as a quantitative method to justify and finalize the findings. Accessibility, inclusiveness, visibility, and use of the space are the factors found responsible for identifying the degree of publicness of the spaces. Here the questioned balance could not be determined merely by using quantitative methodology. The reason lies with the inability of the spaces that could be called solely private or public, followed by the findings in a qualitative way. Henceforth, the balance exists through the in-between public and private spaces, which are also found to be responsible for creating a link and detachments between adjacent spaces. The factors and definitions found in the research can also be used to identify these in-between spaces. Furthermore, the scale used to study each space is also responsible for defining their publicness and, ultimately, the balance.